Lo comunitario y sus saltos creativos - Villasante, Tomás R. (Cuadernos de Trabajo Social, 2006)
In this text, two schematic outlines are presented which introduce and articulate between the two a series of key concepts to distinguish some advances that we are making in participatory methodologies. In the first table, 12 theoretical-practical currents are presented which have been influencing a network of professionals and with which we have been building some methodologies that we understand as developing some avenues in the participatory processes. Next, some of these practical positions and their concepts are laid out, in order to distinguish in concrete terms where we are moving as far as articulating methodologies. In the second table, the relationship between the time periods in a community process are described and what can be best done at each step, at a minimum which questions we should not be asking from the beginning until the collective construction is gelled. At each step in the process the table seeks to show the articulation between the preconceptions, the methodologies, the techniques and the results that can be expected.